2014
DOI: 10.1096/fj.13-243626
|View full text |Cite
|
Sign up to set email alerts
|

The P2Y 13 receptor regulates phosphate metabolism and FGF‐23 secretion with effects on skeletal development

Abstract: Purinergic signaling mediates many cellular processes, including embryonic development and regulation of endocrine signaling. The ADP P2Y13 receptor is known to regulate bone and stem cells activities, although relatively little is known about its role in bone development. In this study we demonstrate, using contemporary techniques, that deletion of the P2Y13 receptor results in an age-dependent skeletal phenotype that is governed by changes in phosphate metabolism and hormone levels. Neonatal and postnatal (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…An in vivo study on phosphate metabolism in ADP P2Y13 receptor-knockout mice demonstrated that young mice with 16 % higher serum phosphorous level compared to mature mice had 73 % fewer osteoclasts [52].…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo study on phosphate metabolism in ADP P2Y13 receptor-knockout mice demonstrated that young mice with 16 % higher serum phosphorous level compared to mature mice had 73 % fewer osteoclasts [52].…”
Section: Discussionmentioning
confidence: 99%
“…The authors discussed the need for further studies to investigate the role of increased FGF23 levels on bone homeostasis [27]. Second, the P2Y 13 receptor has been shown to regulate phosphate metabolism and FGF23 secretion, with significant effects on skeletal development; in this comparison between WT and P2Y 13 KO mice, the KO mice displayed significantly more osteoblasts and less osteoclasts than WT, while their FGF23 level was 65 % higher [28]. However, in these P2Y 13 KO mice, phosphate levels increased and alkaline phosphatase decreased, thus requiring to be cautious on a potential direct link between FGF23 and osteoclasts in this model.…”
Section: Discussionmentioning
confidence: 99%
“…A follow up study by the same group demonstrated that P2Y13 knockout mice display enhanced osteogenic responses to mechanical loading which the authors attribute to reduced levels of extracellular ATP metabolism . The P2Y13 receptor has also been shown to play an important role in phosphate metabolism (Wang et al, 2014) and the terminal differentiation of osteoprogenitor cells into osteoblasts or adipocytes (Biver et al, 2013).…”
Section: P2y Receptors and Osteoblastsmentioning
confidence: 99%